(untitled) (Current Problems in Rail Vehicles, 2025)
This paper deals with some of the implications of the upcoming legislative requirement concerning the design of the tram front ends and LSV with respect to pedestrian collisions. This legislation may lead to the need to use a validated dummy model, which is not yet available. Therefore, the possibility of adopting solutions from the automotive industry is indicated.